Attack on Titan. Part 2 : [videorecording (DVD)] the movie - Miura, Haruma; Hasegawa, Hiroki, 1977-; Hongo, Kanata (Funimation, 2016)
The battle continues between the Scouting Regiment and the Titans. A vengeful soldier apart of the Scouting regiment, Eren, finds a decieving secret about his own regime. Unsure what to do, will the Scouting Regiment win this battle against the Titans?